2022
DOI: 10.1111/apt.17236
|View full text |Cite
|
Sign up to set email alerts
|

Gut metagenome‐derived signature predicts hepatic decompensation and mortality in NAFLD‐related cirrhosis

Abstract: Summary Background There are limited data on the diagnostic accuracy of gut microbial signatures for predicting hepatic decompensation in patients with cirrhosis. Aims To determine whether a stool metagenome‐derived signature accurately detects hepatic decompensation and mortality risk in cirrhosis secondary to non‐alcoholic fatty liver disease (NAFLD) Methods Shotgun metagenomic sequencing was performed on faecal samples collected at study entry from a prospective cohort of adults with NAFLD‐related cirrhosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Using data resampling, we also investigated the impact of sample size in a metabolomics study and found that having 5 samples in a metabolomics study is enough to purify half of the MS/MS spectra and effectively improve spectra quality (Text S7). 21,29 If a feature table is provided, DNMS2Purifier can start with the second step, assigning the corresponding MS/MS spectra to each metabolic feature provided. Next, DNMS2Purifier cleans the MS/MS spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using data resampling, we also investigated the impact of sample size in a metabolomics study and found that having 5 samples in a metabolomics study is enough to purify half of the MS/MS spectra and effectively improve spectra quality (Text S7). 21,29 If a feature table is provided, DNMS2Purifier can start with the second step, assigning the corresponding MS/MS spectra to each metabolic feature provided. Next, DNMS2Purifier cleans the MS/MS spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Using data resampling, we also investigated the impact of sample size in a metabolomics study and found that having 5 samples in a metabolomics study is enough to purify half of the MS/MS spectra and effectively improve spectra quality (Text S7). , It should also be noted that the prediction performance of the trained XGBoost model might be reduced for metabolomics data generated in different LC/MS instruments. In particular, the intensity ratio RSDs used for prediction is instrument-dependent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disadvantaged and under-served communities are often disproportionately affected by liver disease but often lack timely access to appropriate care 91 , 101 , 102 . Despite advances in the diagnosis, treatment and management of cirrhosis, medical interventions often have limited benefit on long-term survival, necessitating the use of resource-heavy treatments such as liver transplantation 7 , 103 106 . Therefore, the focus of care should be shifted upstream, from the management of complications to prevention and early treatment 74 .…”
Section: Future Directionsmentioning
confidence: 99%